An ecological momentary assessment study of affectively-charged motivational states and physical activity. (July 2023) - Crosley-Lyons, Rachel; Do, Bridgette; Hewus, Micaela; Dunton, Genevieve F.
Abstract: The physical activity (PA) intention-behavior gap has prompted researchers to explore other explanatory factors such as affective mechanisms which might better explain PA engagement. Affectively-charged motivations (e.g., desire, dread) are thought to influence the pursuit or avoidance of future behavior. This study examined whether affectively-charged motivations for PA changed across the day and were differentially associated with PA intensity. Participants (N = 60) wore ActiGraph GT3X accelerometers and answered EMA (M = 134.7 prompts/person) about affectively-charged motivations for upcoming PA using a 0-to-100-point scale (dread-excitement) in the morning, pre-activity, at-random, and evening for 14 days. Affectively-charged motivations for PA were lower in the morning and at-random compared to pre-activity ( p = .004) and evening ( p < .001). On average, individuals who rated morning affectively-charged motivations for PA 10-points higher engaged in 28 additional min/week of moderate-to-vigorous PA ( p = .048). These findings suggest that affectively-charged motivations occurring in the morning may have greater salience for PA. Highlights: Affectively-charged motivations for physical activity vary in strength across the day. Desire for physical activity is lowest in the morning and highest in the evening. Elevated morning motivation is associated with more moderate-to-vigorous activity.